Field-simulated droughts affect elemental leaf stoichiometry in Mediterranean forests and shrublands - Sardans, Jordi; Rivas-Ubach, Albert; Estiarte, Marc; Ogaya, Romà; Penuelas, Josep (ACTA OECOLOGICA-INTERNATIONAL JOURNAL OF ECOLOGY, 2013)
This study evaluated the change induced by the year season and by experimentally induced drought on foliar element stoichiometry of the predominant woody species (Quercus ilex and Erica multiflora) in two Mediterranean ecosystems, a forest and a shrubland. This study is based in two long-term (11 yr) field experiments that simulated drought throughout the annual cycle. The effects of experimental droughts were significant but weaker than the changes produced by ontogeny and seasonality. Leaf N and P concentrations were higher in spring (the main growing season) in E. multiflora and, in Q. ilex in autumn (a period of additional growth). Leaf N:P ratios were lower in spring. In Q. ilex, the highest leaf K concentrations and leaf K:P ratios, and the lowest leaf C:K and N:K ratios, occurred in summer, the season when water stress was greatest. In E. multiflora, leaf K concentrations and K:P ratios were highest, and leaf C:K and N:K ratios were lowest in the plants from the drought-treated plots. The plant capacity to change K concentrations in response to seasonality and to drought is at least as great as the capacity to change N and P concentrations. The results underscore the importance of K and its stoichiometry relative to C, N and P in dry environments. These results indicate first, that N:P ratio shifts are not uniquely related to growth rate in Mediterranean plants but also to drought, and second, that there is a need to take into account K in ecological stoichiometry studies of terrestrial plants. (C) 2013 Elsevier Masson SAS. All rights reserved.
Keywords: climate change; Drought; Growth rate hypothesis; N:P; nitrogen; Ontogeny; phosphorus; Potassium

Increasing drought decreases phosphorus availability in an evergreen Mediterranean forest - Sardans, Jordi; Penuelas, Josep (Plant and Soil, 2004)
Mediterranean ecosystems are water-limited and frequently also nutrient-limited. We aimed to investigate the effects of increasing drought, as predicted by GCM and eco-physiological models for the next decades, on the P cycle and P plant availability in a Mediterranean forest. We conducted a ﬁeld experiment in a mature evergreen oak forest, establishing four drought-treatment plots and four control plots (150 m2 each). After three years, the runoff and rainfall exclusion reduced an overall 22% the soil moisture, and the runoff exclusion alone reduced it 10%. The reduction of 22% in soil moisture produced a decrease of 40% of the accumulated aboveground plant P content, above all because there was a smaller increase in aerial biomass. The plant leaf P content increased by 100 ± 40 mg m−2 in the control plots, whereas it decreased by 40 ± 40 mg m−2 in the drought plots. The soil Po-NaHCO3 (organic labile-P fraction) increased by 25% in consonance with the increase in litterfall, while the inorganic labile-P fraction decreased in relation to the organic labile-P fraction up to 48%, indicating a decrease in microbial activity. Thus, after just three years of slight drought, a clear trend towards an accumulation of P in the soil and towards a decrease of P in the stand biomass was observed. The P accumulation in the soil in the drought plots was mainly in forms that were not directly available to plants. These indirect effects of drought including the decrease in plant P availability, may
Keywords: climate change; Drought; Mediterranean ecosystems; mineralomasses; nutrient concentrations; nutrient cycles; phosphorus; Quercus ilex; Soil

Increasing drought decreases phosphorus availability in an evergreen Mediterranean forest - Sardans, Jordi; Penuelas, Josep (Plant and Soil, 2004)
Mediterranean ecosystems are water-limited and frequently also nutrient-limited. We aimed to investigate the effects of increasing drought, as predicted by GCM and eco-physiological models for the next decades, on the P cycle and P plant availability in a Mediterranean forest. We conducted a ﬁeld experiment in a mature evergreen oak forest, establishing four drought-treatment plots and four control plots (150 m2 each). After three years, the runoff and rainfall exclusion reduced an overall 22% the soil moisture, and the runoff exclusion alone reduced it 10%. The reduction of 22% in soil moisture produced a decrease of 40% of the accumulated aboveground plant P content, above all because there was a smaller increase in aerial biomass. The plant leaf P content increased by 100 ± 40 mg m−2 in the control plots, whereas it decreased by 40 ± 40 mg m−2 in the drought plots. The soil Po-NaHCO3 (organic labile-P fraction) increased by 25% in consonance with the increase in litterfall, while the inorganic labile-P fraction decreased in relation to the organic labile-P fraction up to 48%, indicating a decrease in microbial activity. Thus, after just three years of slight drought, a clear trend towards an accumulation of P in the soil and towards a decrease of P in the stand biomass was observed. The P accumulation in the soil in the drought plots was mainly in forms that were not directly available to plants. These indirect effects of drought including the decrease in plant P availability, may
Keywords: climate change; Drought; Mediterranean ecosystems; mineralomasses; nutrient concentrations; nutrient cycles; phosphorus; Quercus ilex; Soil